2008
DOI: 10.1161/atvbaha.107.159913
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Epoxide Reductase Complex Subunit 1 (VKORC1) Polymorphism and Aortic Calcification

Abstract: Objective-Besides effects on hemostasis, vitamin K-dependent proteins play a role in bone mineralization and arterial calcification. We investigated the association between the VKORC1 1173CϾT polymorphism and calcification of the aortic far wall in a large population-based cohort. Methods and Results-Aortic calcification was diagnosed by radiographic detection of calcified deposits in the abdominal aorta. In all cohort members for whom DNA was available, the C1173T SNP of VKORC1 (rs9934438)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…Previous research already showed more calcification in animals with vitamin K deficiency due to a mutant vitamin K epoxide reductase subcomponent-1. 14,15 In addition, coronary calcifications have been found in patients using vitamin K antagonists, but in contrast to our study, patients were relatively old, had other risk factors for atherosclerosis, or received coumarins for an atherosclerotic cardiovascular indication. 7,16,17 The dp-ucMGP assay described here specifically detects nonphosphorylated and noncarboxylated MGP, which has little or no affinity for calcium salts.…”
Section: Resultscontrasting
confidence: 87%
“…Previous research already showed more calcification in animals with vitamin K deficiency due to a mutant vitamin K epoxide reductase subcomponent-1. 14,15 In addition, coronary calcifications have been found in patients using vitamin K antagonists, but in contrast to our study, patients were relatively old, had other risk factors for atherosclerosis, or received coumarins for an atherosclerotic cardiovascular indication. 7,16,17 The dp-ucMGP assay described here specifically detects nonphosphorylated and noncarboxylated MGP, which has little or no affinity for calcium salts.…”
Section: Resultscontrasting
confidence: 87%
“…This result cautions one in the interpretation of significant associations reported between the main VKORC1 haplotypes and arterial cardiovascular disease, 41,42 as this was thought to require local effects on gene expression and modification of matrix proteins in target tissues. Consistent with this, one association study failed to observe association between VKORC1 genotypes and arterial cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 77%
“…13,14 Furthermore, VKORC1 haplotypes that reduce the activity of the VKORC1 enzyme have been shown to be associated with a significant higher risk of vascular calcification in rats 15 and aortic calcification in humans. 16 Hence, it is possible that similar polymorphisms in genes involved in the phylloquinone metabolism may result in higher phylloquinone status because of reduced phylloquinone recycling or metabolism. Furthermore, it is also possible that higher phylloquinone concentrations are caused by disturbed phylloquinone transport or cellular phylloquinone uptake.…”
Section: Discussionmentioning
confidence: 99%